Characterisasion and Rate Determination of Lipid Extraction From Nannochloropsis Using Stirring Method - Nirmalasari, Jiran; Setyawan, Martomo; Jamilatun, Siti; Suhendra, Suhendra; Othman, Mohamad Rizza (Universitas Ahmad Dahlan, 2023)
The rapid growth of global population causes increasing energy needs. The energy needs currently used depend on fossil fuels which are non-renewable energy sources. An alternative to solve this problem is to use renewable fuel. One alternative to reduce the use of fossil fuels is microalgae. The microalgae used in this research is Nannochloropsis sp. Because it contains quite a lot of lipids, it has the potential to be used as a raw material for making biodiesel 42.315% of the fatty acids contained in Nannochloropsis are palmitoleic. This research was conducted to determine the total lipid content and percent extraction yield. The method used in this research is mixing methods. Extraction times were 30 minutes, 60 minutes, 90 minutes and 120 minutes. The greatest total lipid content was obtained at 120 m inutes with the amount obtained being 10.46%. Meanwhile, the highest percentage of results obtained was at 120 minutes, namely 10.46%. The optimum extraction speed is in the range of 0 to 30 minutes with a speed of 0.0305% with a lipid recovery of around 90% of the lipids produced.. The research results obtained showed that the extraction time affected the results obtained in terms of total lipid content and percent yield. The longer the extraction time, the greater the lipid content and percent yield obtained.